PENINGKATAN KESIAPSIAGAAN BENCANA MELALUI PEMETAAN JALUR EVAKUASI: STUDI KASUS SMA NEGERI 5 BANDAR LAMPUNG - Phelia, Arlina; Darmaputra, I Gde; Raharjo, Ismadi; Idrus, Muhammad; Kuswadi, Didik; Putri, Vera Chania (Jurnal Abdi Insani, 2025)
SMA Negeri 5 Bandar Lampung is located in a strategic yet disaster-prone area, facing risks such as floods, earthquakes, and fires. The school did not have a structured evacuation route system or evacuation maps displayed in strategic areas, leaving the school community without clear visual guidance for evacuation routes and assembly points during emergencies. This community service activity aimed to develop evacuation route maps based on the actual spatial conditions of the school to improve preparedness. The methods included field observation, manual measurement, visual documentation, and digital mapping using AutoCAD, with design validation involving school stakeholders. The activity produced a proportional digital evacuation map showing routes from all strategic areas to three designated assembly points. Before the implementation, only 16.7% of evacuation-supporting elements were available; after installation and dissemination, the preparedness index improved significantly from an average of 22.7% to 76.7%. The map is clear, easy to understand, and serves as an essential visual reference to support the Disaster-Safe School program. The development of this evacuation route map has improved the structural preparedness of the school and provides a technical foundation for future disaster drills and training.